2015
DOI: 10.1007/s10597-015-9911-3
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Ideation Among Adults with Disability in Western Canada: A Brief Report

Abstract: This study investigated prevalence and risk factors for suicidal ideation among adults with self-reported disability in Western Canada. The method was secondary data analysis utilising the Canadian Community Health Survey. The odds of 12-month suicidal ideation are 3.5 times greater for adults with self-reported disability compared with non-disabled adults, controlling for age, sex, ethnicity, and psychiatric morbidity. The heightened risk of ideation among adults with self-reported disability is partially exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 26 publications
3
40
0
Order By: Relevance
“…This study explored suicidal ideations among mothers living with physical disabilities in the Greater Accra Region of Ghana which highlighted the commonality of the issue among this category of mothers. This is similar to other findings since adults with disabilities have been found to have higher rates of suicidal thoughts compared to their counterparts who have no disabilities [ 8 , 9 ]. Perhaps disability poses challenges to those who live with it and such challenges may predispose them to depression and subsequent suicidal thoughts.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study explored suicidal ideations among mothers living with physical disabilities in the Greater Accra Region of Ghana which highlighted the commonality of the issue among this category of mothers. This is similar to other findings since adults with disabilities have been found to have higher rates of suicidal thoughts compared to their counterparts who have no disabilities [ 8 , 9 ]. Perhaps disability poses challenges to those who live with it and such challenges may predispose them to depression and subsequent suicidal thoughts.…”
Section: Discussionsupporting
confidence: 91%
“…Some individuals perceive suicide as acceptable in a situation where there is a disability [ 7 ]. Adults with disabilities have higher rates of suicidal ideations compared to those without disabilities [ 8 , 9 ]. For each successful suicide, there could be many ideations and attempts.…”
Section: Introductionmentioning
confidence: 99%
“…8 Although chronic pain is common after TBI, its role in both SI and SA seems to be related more to an individual's perception or acceptance of pain, rather than pain severity, 9 which is in turn associated with disability, 10 an additional known risk factor for suicidality. 11,12 Severity of TBI has not been linked consistently to depression or risk of suicidality, 7,13,14 but other injury-related factors (eg, severity of extracranial injury [ECI]) that may lead to both increased distress and greater disability have not been assessed in previous studies.…”
mentioning
confidence: 99%
“…A four-nation study showed that impaired physical functioning and dual sensory loss were associated with greater odds of depressive symptoms in home care clients (47). Suicide attempts may cause disability among survivors, but also there is increased risk of suicide among persons living with physical disabilities (48)(49)(50)(51) for reasons that include pain and a sense of burden to others (52,53).…”
Section: Physical Health and Disabilitymentioning
confidence: 99%